2021
DOI: 10.1038/s41430-021-00993-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin C in pneumonia and COVID-19 infection in adults with European ancestry: a Mendelian randomisation study

Abstract: Background High dose vitamin C infusion has been proposed to treat critically ill patients, including patients with pneumonia and severe COVID-19. However, trials have shown mixed findings. Here we assessed the unconfounded associations of vitamin C with COVID-19 and pneumonia using the Mendelian randomisation approach. Methods This is a separate-sample Mendelian randomisation study using publicly available data. We applied single nucleotide polymorphisms (SNPs) that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…Based on their Mendelian randomization study, Hui et al concluded that there is no support for the use of vitamin C in the prevention and treatment of pneumonia or COVID-19 [1]. However, their study has limitations.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their Mendelian randomization study, Hui et al concluded that there is no support for the use of vitamin C in the prevention and treatment of pneumonia or COVID-19 [1]. However, their study has limitations.…”
Section: To the Editormentioning
confidence: 99%
“…Hui et al [1] used single nucleotide polymorphisms (SNPs) that were associated with plasma vitamin C level in the genome-wide association study in 52,018 people of European ancestry [2]. However, the cited study states "the variance of plasma vitamin C explained by the 11 lead SNPs was 1.87% on average" [2].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study revealed that surplus Zinc supplementation can decrease IFN-γ expression in younger subject whereas in elderly persons increased interferon-alpha (IFN-α) production by leukocytes. However award-risk ratio is in favor of Zinc supplementation in COVID-19 [190] , [191] . There are less preclinical and clinical data on this aspect and results from currently ongoing trials employing Zinc in COVID-19 will throw light on the efficacy against viral infections in vivo.…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%
“…The goal of this paper is to demonstrate the bias against vitamin C by using examples primarily from the trials on vitamin C for infections. Some reviews and studies on vitamin C and respiratory infections [10][11][12][13][14][15] have been flawed [16][17][18][19][20][21][22][23], but this paper does not systematically review the effect of vitamin C on infections, since this is covered in other publications [4][5][6][7][8][9][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%